2021
DOI: 10.3390/agronomy11071413
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of N Fertilizer Application Timing on Wheat Yield on Chernozem Soil

Abstract: The challenges of the global food supply and environment conservation require ongoing scientific observations of soil-to-plant and plant-to-environment interactions with the aim of improving agriculture resource management. This study included observations of winter wheat yield and biomass of four varieties over three consecutive growing seasons and four site-year cases to assess the effects of nitrogen (N) fertilization rate and time of application on grain yield and biomass. For different wheat varieties, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Overall, average grain yield was 53%, and biomass was 17% greater in 2020 compared with 2019, but biomass differences were apparent only for fertilizer rates above the control. A significant environment by N application effect on wheat biomass, NR, and NUtE was reported with prior studies (Bryant‐Schlobohm et al., 2020; Hawkesford & Riche, 2020; Kostić et al., 2021). Harvest indices were significantly higher with the unfertilized control and remained fairly constant with N application possibly because of greater vegetative growth that increased the proportion of stover with N application rate compared with the unfertilized control.…”
Section: Discussionsupporting
confidence: 72%
“…Overall, average grain yield was 53%, and biomass was 17% greater in 2020 compared with 2019, but biomass differences were apparent only for fertilizer rates above the control. A significant environment by N application effect on wheat biomass, NR, and NUtE was reported with prior studies (Bryant‐Schlobohm et al., 2020; Hawkesford & Riche, 2020; Kostić et al., 2021). Harvest indices were significantly higher with the unfertilized control and remained fairly constant with N application possibly because of greater vegetative growth that increased the proportion of stover with N application rate compared with the unfertilized control.…”
Section: Discussionsupporting
confidence: 72%
“…Fertilizers represent a category of inputs with a decisive role in defining agricultural productions, their quality, economic yields, differentiated in relation to the crop plant, the category of agricultural products, and the level of analysis [74,75]. Strong (and very strong) correlations were found between fertilizers and wheat production, respectively, and production quality indices, in different experimental conditions, regarding the location, soil types, cultivated wheat genotypes, types of fertilizers, and cultivation technologies [76][77][78]. Based on the strong correlations between biomass, grain production, and wheat quality indices, it has been suggested that biomass can be used as an indicator of cereal response to N in terms of yield [79].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works addressed the effects of split application on wheat grain yield and grain N concentration (Colecchia et al., 2015; Hooper et al., 2015; Xia et al., 2017). Split N application at sowing and tillering or at tillering and stem elongation is a usual practice in wheat crops (Kostić et al., 2021; Lopez‐Bellido et al., 2012; Schulz et al., 2015) because wheat begins to require more N at the end of tillering when biomass production strongly increases, and the root system is sufficiently dense to extract the applied N (Muñoz‐Romero et al., 2010). More recent works reported that weather conditions and total N input are more relevant than timing and fractioning of N fertilizer on grain yield and protein content (Lopez‐Bellido et al., 2012; Tedone et al., 2014).…”
Section: Introductionmentioning
confidence: 99%